Characteristics of foraging habitats and chick food provisioning by tropical Roseate Terns - Ramos, Jaime (2015)
I studied tropical Roseate Terns (Sterna dougallii) on Aride Island, Seychelles, between 1997-1999. Productivity in 1998 was 0.58 fledglings/breeding pair, and in 1999 no young fledged. Roseate Terns on Aride concentrated their foraging along the coastline exposed to prevailing winds, with flock size over this area being significantly correlated with amount of food offered to chicks. In 1998, Lesser Noddies (Anous tenuirostris) were present in 91% of the Roseate Tern flocks, but in 1999 occurred in only 32%. During the 1998 successful breeding season, Roseate Terns were associated with dense flocks of Lesser Noddies over predatory fish, whereas during the 1999 failure season most Roseate Tern hocks were either monospecific or mixed with Fairy Terns (Gygis alba), and without predatory fish. The mean flock size of Roseate Terns (82 vs. 6 birds) and the rate of foraging attempts (8.3 vs. 2.8 attempts min(-1)) were significantly greater in association with predatory fish. Mullidae (Parupeneus or Mulloidichthys) were the primary prey taken by Roseate Terns, and alternative sources of food were apparently scarce. The high daily variations in the amount of food brought to chicks, intermediate periods of low food delivery, and an apparent seasonal decline in the amount of food brought to the colony suggest that food is unpredictable on a daily and seasonal basis. Absence of predatory fish may explain complete breeding failures and periods of low food delivery, but the importance of other factors is unknown. Information on the ecology and movement patterns of predatory fish around Aride Island is needed to assist the conservation of the Roseate Terns.